STUDENTS’ GEOMETRIC THINKING BASED ON VAN HIELE’S THEORY - Harina Fitriyani; Sri Adi Widodo; Aan Hendroanto (Jurnal Infinity, 2018)
The current study aims to identify the development level of students’ geometric thinking in mathematics education department, Universitas Ahmad Dahlan based on van Hiele’s theory. This is a descriptive qualitative research with the respondents as many as 129 students. In addition to researchers, the instrument used in this study is a test consisting of 25 items multiple choice questions. The data is analyzed by using Milles and Huberman model. The result shows that there were 30,65% of students in pre-visualization level, 21,51% of students in visualizes level, and 29,03% of students in analyze level, 16,67% of students in informal deduction level, 2,15% of students in deduction level, and 0,00% of student in rigor level. Furthermore, findings indicated a transition level among development levels of geometric thinking in pre-analyze, pre-informal deduction, pre-deduction, and pre-rigor that were 20%; 13,44%; 6,45%; 1,08% respectively. The other findings were 40,32% of students were difficult to determine and 4,3% of students cannot be identified.